Key Insights From a Decade of Breast Augmentation: Our 5 Critical Decisions in Breast Implant Selection - Bletsis, Patrick P.; van der Lei, Berend (Plastic and reconstructive surgery. Global open, 2025)
Breast augmentation continues to rank among the most commonly performed procedures. A crucial factor in achieving successful outcomes lies in a methodical implant-selection system, a principle underscored by Tebbetts and Adams in their TEPID and High Five systems. We have revisited several factors during years of experience. Thorough preoperative consultations play a pivotal role, involving discussions on the patient's motivation for breast augmentation and their medical history. Subsequently, medical photographs are taken, and 5 critical breast measurements are recorded: sternal notch-nipple distance, base width of the breast, soft-tissue coverage of the implant, optimal implant selection based on volume and dimensions, and calculation of the neo-inframammary fold using the Pythagorean theorem. Our system goes beyond traditional approaches by offering patients the chance to preview the postoperative result through both bra sizers and 3-dimensional simulation. Shared decision-making is another integral aspect of our methodology, providing patients with a voice in the medical decision-making process. During the period from 2009 to 2019, the senior author conducted primary breast augmentations on 716 patients, with follow-ups extending up to 3 years. Notably, 1.5% (11 patients) required reoperation, and only 0.03% (2 patients) underwent reoperation specifically for implant size exchange. Our system's strength lies in its reliance on straightforward tissue-based measurements and a commitment to incorporating patient preferences through interactive decision-making. We aim to contribute to the professional development of fellow plastic surgeons and residents by sharing our 5 critical decisions, confident in their potential value for enhancing their practice.